Learning: II. Problem Solving and Related Topics. - Corman, Bernard R. (Review of Educational Research, 1958)
This article reviews the research on problem solving and its related topics. If a general problem-solving ability is assumed, it becomes reasonable to raise questions about the characteristics of good and poor problem solver. The relationship of rigidity and problem solving was extensively researched by the author. In several studies, an attempt to discern shifts in performance after training designed to change attitudes. A number of studies were reported in which the variable manipulated was the atmosphere in which the problem solving occurred.